Litigation and Settlement under Judicial Agency - Levent Koçkesen; Murat Usman (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
We model the settlement of a legal dispute where the trial outcome depends on the behavior of a strategically motivated judge. We consider a standard asymmetric information model where the uninformed defendant makes a take it or leave it offer. If the case goes to trial, the judge decides how much effort to exert to learn about the actual damages inflicted on the plaintiff. We show that under very general assumptions the model exhibits multiple equilibria. In equilibria in which the judge exerts less effort more cases settle out of court, and vice versa. The judge is better off in low effort equilibria, with a higher settlement rate. However, the terms of the settlement heavily favor the informed plaintiff, and consequently induce over-investment in ex ante preventive care by the defendant.
Keywords: K00; K41; D82; C78; 330; Litigation; settlement; trial; judges; Zivilprozess; Rechtsprechung; Verhandlungstheorie; Rechtsökonomik; Theorie